0633 Prospective Semester-Long Evaluation of College Student Sleep. (12th April 2019) - *Gibney, Sean F; *Czeisler, Mark E; *Fang, Kristen; Clerx, Emma M; Allan, James S; Yan, Allison; Lee, Jeongmin; So, Raymond J; Weaver, Matthew D; Viyaran, Natalie; Qadri, Salim; O'Brien, Conor S; et al.
Abstract: Introduction: Sleep duration and regularity are important for learning, development, and mental health. Recent work has revealed that both sleep duration and consistency of sleep timing are suboptimal in many college students. We characterized sleep duration and timing in college students over an entire semester. Methods: We recruited students through online and in-person approaches, with most enrollment from in-person solicitations outside campus dining areas. Demographic information, sleep habits, external factors affecting sleep and chronotype were assessed via questionnaire. Throughout the semester, daily emails were sent to participants with a link to complete electronic sleep diaries. Incentives were offered for diary completion. Results: 391 students (55% female) completed 7, 390 daily sleep diaries. Most participants (65.7%) expected to graduate within the next one or two years. At baseline, most students (60%) reported sleeping less than they need to feel well-rested. The most common factors influencing sleep related to academic (82%) and social (67%) commitments. Noise was the most commonly reported environmental barrier, with 65% reporting that noise adversely affected their sleep. When class was in session, students averaged 7.2h± 1.7h of sleep during the week and 7.7h± 1.7h of sleep on weekends. Sleep was significantly increased during spring recess (mean 8.1h± 2.0h). Sleep duration varied by chronotype (p<0.001), with morning chronotypes averaging the longest sleep duration (8.0h± 1.2h). Overall, there was no change in average sleep duration as collected on daily diaries over the semester. On the post-study questionnaire, over 50% of students reporting sleeping on a more consistent schedule and sleeping longer each night as a result of participating in the study. Conclusion: Sleep deficiency and circadian disruption are common among college students. Academic, social, and environmental factors limit the opportunity for and foster inconsistent timing of sleep. Morning chronotypes may be more likely to achieve sufficient sleep in the college setting. Appropriate interventions may be possible. Support (If Any): *Indicates equal contribution to the work. Supported by NIH R01-GM-105018, K24-HL-105664 (EBK)